Clinical psychology in Lithuania - Gailienė, Danutė (Psichologija, 1997)
The situation and development of clinical psychology in Lithuania is inextricably related to the socio-political situation of the country and its rather dramatic history. The article describes the beginnings of Professional psychology in Lithuania after re-establishing and independent state in 1918, the situation of psychology under the soviet occupation, the beginning of clinical psychology, the new development of clinical psychology after regaining independence in 1 991, and the present situations and problems of clinical psychology in Lithuania.
Keywords: clinical psychology; history of psychology